Approaches to Next-Generation Capripoxvirus and Monkeypox Virus Vaccines - Anna-Lise Williamson (Viruses, 2025)
Globally, there are two major poxvirus outbreaks: mpox, caused by the monkeypox virus, and lumpy skin disease, caused by the lumpy skin disease virus. While vaccines for both diseases exist, there is a need for improved vaccines. The original vaccines used to eradicate smallpox, which also protect from the disease now known as mpox, are no longer acceptable. This is mainly due to the risk of serious adverse events, particularly in HIV-positive people. The next-generation vaccine for mpox prevention is modified vaccinia Ankara, which does not complete the viral replication cycle in humans and, therefore, has a better safety profile. However, two modified vaccinia Ankara immunizations are needed to give good but often incomplete protection, and there are indications that the immune response will wane over time. A better vaccine that induces a long-lived response with only one immunization is desirable. Another recently available smallpox vaccine is LC16m8. While LC16m8 contains replicating vaccinia virus, it is a more attenuated vaccine than the original vaccines and has limited side effects. The commonly used lumpy skin disease vaccines are based on attenuated lumpy skin disease virus. However, an inactivated or non-infectious vaccine is desirable as the disease spreads into new territories. This article reviews novel vaccine approaches, including mRNA and subunit vaccines, to protect from poxvirus infection.